Integrating Community Engagement into National Security Policy: A Preventive Approach to Violent Extremism: https://doi.org/10.5281/zenodo.16886114 - Ibrahim Shah; Muhammad Uzair (Journal of Religion and Society, 2025)
Violent extremism is a major security issue that needs new solutions to combat the problem at its source other than the manifestations. This paper discusses the need to include community engagement as part of the national security policy as a prevention of radicalization because community-based and participatory methods have a more lasting effect than securitized methods. The study, using case studies (such as the UK Prevent Strategy, Denmark Aarhus Model, Indonesia deradicalization villages) based on qualitative analysis, determines the main success factors, which are: multi-agency coordination, cultural adaptation, structural firewalls between community programs and intelligence operations. The results indicate that effective programs are long term social investments, they use local knowledge, and they focus on socioeconomic factors that drive extremism and not just ideological discourse. Nevertheless, there are still some obstacles, such as a lack of trust in securitized policies by the community, unstable funding, and insufficient response to digital radicalization and right-wing extremism. The discussion also presents conflicts of security necessity and grassroots involvement, where it suggests to shift the paradigm of surveillance-based models to community-based prevention. The policy advice should be on institutionalization of transparency mechanisms, co-designing intervention with affected communities, and establishing independent oversight to curb discriminatory practices. Although there are limitations to the study, which include cross-national comparability and the long-term effects, the study highlights the transformative power of community-based approaches. This research helps to inform the changing discourse of how to counter violent extremism by focusing more on empowering social cohesion than coercion by reimagining the foundations of security. Keywords: Community Engagement, Violent Extremism, National Security Policy, Radicalization Prevention, Social Capital, Public Health Approach, Securitization, Counterterrorism, Participatory Governance, Trust-Building